Effects of posture on flow-volume curves during normocapnia and hypercapnia in patients with obstructive sleep apnoea. Issue 7 (July 1992) - Miura, C; Hida, W; Miki, H; Kikuchi, Y; Chonan, T; Takishima, T
Abstract : BACKGROUND: A high ratio of forced expiratory to forced inspiratory maximal flow at 50% of vital capacity (FEF50/FIF50) may identify upper airway dysfunction. Since hypercapnia increases the motor activity of airway dilating muscles its effects on the maximum expiratory and inspiratory flow-volume curves (MEIFV) in patients with obstructive sleep apnoea and in normal subjects in different postures was studied. METHODS: The effects of posture on the maximum expiratory and inspiratory flow-volume curves during the breathing of air and 7% carbon dioxide in 11 patients with obstructive sleep apnoea were compared with those in nine normal subjects. Measurements were made in the sitting, supine, and right lateral recumbent positions. Forced expiratory flow at 50% vital capacity (FEF50), forced inspiratory flow at 50% vital capacity (FIF50) and FEF50/FIF50 were determined. RESULTS: In the normal subjects FEF50, FIF50, and FEF50/FIF50 were not affected by change in posture or by breathing carbon dioxide. In the patients there was a fall in FIF50 and an increase in FEF50/FIF50 when breathing air in the supine position compared with values in the seated and lateral position. While they were breathing carbon dioxide there was a slight increase in FEF50 when patients were seated or in the lateral position compared with values during air breathing. Hypercapnia abolished the effects of posture on FEF50/FIF50. Values for FEF50/FIF50 in the supine position while they were breathing air correlated with the apnoeic index but not with other polysomnographic data. CONCLUSION: In patients with obstructive sleep apnoea the upper airway is prone to collapse during inspiration when the patient is supine, even when awake; this tendency can be reversed by breathing carbon dioxide.